Artificial intelligence and analysis of body position to determine the speed of the strike in Karate - Dr Mohammed Ghazi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. The techniques of artificial intelligence in educational hardware and software are able to deduce knowledge and skills, and the importance of the study is due to the use of artificial intelligence techniques in analyzing the situation of skill performance, the use of artificial intelligence techniques in the system of skill analysis of the skills under study, the link of artificial intelligence with kinetic variables For the skills under study and the study aimed to apply artificial intelligence techniques in skill analysis, building an artificial intelligence system from motor variables and motor performance. Materials and methods. The study samples The researcher determined the study population of karate players by choosing the study sample in a random way from karate players in Kafr El-Sheikh Sports Club. Results. Performance through data and recommendations came to use artificial intelligence techniques in various games and areas of physical education. Conclusions. Artificial intelligence techniques work on skill analysis through programming neurons. Deep learning gives indications of improving performance through data. The use of artificial intelligence techniques in various games and areas of physical education